Development of Media Learning for Facial Makeup Based on Google Sites Application Software to Improve Students' Abilities - Maghfiroh, Anik; Tumangger, Mia Hafizah; Ihsani, Ade Novi Nurul; Purnawirawan, Okta (Universitas Negeri Semarang, 2025)
This study aims to improve students' skills through software-based make-up learning media with the help of the Google Site application. The research method used is research and development (R&D) with the ADDIE model. The approach used is a quantitative approach. The results of this study were obtained from the values ​​of 8 media expert validators, by obtaining data with an average coefficient value of 0.90-0.95. Valid data related to learning media was obtained based on the results of expert validators getting high valid values. The trial in this study amounted to 70 beauty education student participants getting high average values, so it can be concluded that make-up media can improve students' abilities.